(untitled) (Editora Impacto Científico, 2025)
The present study aimed to analyze the fundamental principles of infant feeding, based on official guidelines. The methodology consisted of an in-depth bibliographic research of reference documents, such as the Dietary Guidelines for Brazilian Children Under 2 Years of Age (2019), and specialized publications in the SciELO database, focusing on the World Health Organization (WHO) recommendations concerning breastfeeding and complementary feeding practices. The results indicate that the initial period of life is crucial for health programming throughout the life cycle. The guidelines establish a rigorous protocol that demands exclusive breastfeeding up to six months and precision in the timing of complementary food introduction. Nutritional success is determined by the prohibition of sugars and ultra-processed foods, the prioritization of in natura foods, and the valuation of the social dimension of meals. It is concluded that infant nutrition transcends the mere ingestion of nutrients, asserting itself as a health-programming determinant that requires the protection of the child’s vulnerability and strict adherence to quality protocols. DOI: https://doi.org/10.56238/edimpacto2025.090-027